Diagnostics of peak laser intensity by pair production from thin foil target. (24th April 2020) - Lécz, Zsolt; Andreev, Alexander
Abstract: It is known that in the small quantum parameter regime the Breit-Wheeler electron-positron pair creation cross section is extremely sensitive on the photon energy and on the background field. We present the dependence of positron yield on laser intensity in laser-foil interactions with the help of analytical theory and particle-in-cell simulaitons. These particles are emitted in a relatively narrow range of cone angles close to perpendicular direction relative to the laser beam axis. This allows for establishing an in situ intensity diagnostic by measuring the positron current in experiments where peta-watt class lasers are used.